Developing competency to shape practice: third-space professionals and education for sustainable development - Joanna Wilson-Scott (Journal of Learning Development in Higher Education)
Within higher education institutions, commitments and approaches to education for sustainable development vary, and policies do not always filter down to pedagogical practice and the student learning experience. Third-space professionals such as educational and academic developers are well-placed to work with those engaged in teaching and the support of learning across all subject areas and schools, to develop key competences in the area of education for sustainable development. However, certain challenges exist, particularly third-space professionals’ own need to develop such key competences, and limitations surrounding the time required to do so. This piece calls for more conversations on how such challenges can be overcome, in order for third-space professionals to collaborate with and most effectively prepare higher education teachers to support education for sustainable development and best equip graduates with sustainable competences of their own.